2019
DOI: 10.1016/j.ejor.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Combining uncertainty with uncertainty to get certainty? Efficiency analysis for regulation purposes

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…The impact of the model misspecification on the estimated T E was studied, using simulations, among other papers in Yu (1998); Ruggiero (1999); Ondrich and Ruggiero (2001); Andor and Parmeter (2017); Andor et al (2019). Ruggiero (1999) concluded, that if data are generated by normalhalf-normal model, then T E estimates by true (normal-half-normal) and misspecified (normal-exponential) models provide similar results.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The impact of the model misspecification on the estimated T E was studied, using simulations, among other papers in Yu (1998); Ruggiero (1999); Ondrich and Ruggiero (2001); Andor and Parmeter (2017); Andor et al (2019). Ruggiero (1999) concluded, that if data are generated by normalhalf-normal model, then T E estimates by true (normal-half-normal) and misspecified (normal-exponential) models provide similar results.…”
Section: Introductionmentioning
confidence: 95%
“…Some papers (Yu, 1998;Ruggiero, 1999;Ondrich and Ruggiero, 2001) use rank correlation between true and estimated values of T E as a measure of the model misspecification. Other papers (Andor and Parmeter, 2017;Andor et al, 2019) use root mean square error (RMSE) measure as the distance between true and estimated T E for performance comparison of different models. Giannakas et al (2003) demonstrated that predictions of T E are sensitive to the misspecification of the functional form of the production function in stochastic frontier regression.…”
Section: Introductionmentioning
confidence: 99%
“…The econometric methods of estimating efficiency can roughly be divided into parametric and nonparametric kinds of approaches (see, for instance, Andor and Hesse 2014;Andor et al 2019 andZelenyuk 2019). Both make use of economic production theory and aim to identify potentials of increasing output given a set of inputs.…”
Section: Introductionmentioning
confidence: 99%
“…As there is a long history of research on the production and efficiency analysis, several methods have already been developed, for instance, the classic nonparametric data envelopment analysis (DEA) and the parametric stochastic frontier analysis (SFA) (for a review of these two methods, see Andor and Hesse 2014;Andor et al 2019 andZelenyuk 2019). Filippini and Hunt (2015, p. 58) argue that economic approaches "are a sounder basis for measuring energy efficiency based on economic foundations rather than relying on simple energy intensity indicators.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the CEP in China is rising and the CEP of eastern China was higher than that of central and western China [26]. Although SFA has been widely applied, the outcomes are often easily affected by the selected production function in the above research [27]. Consequently, building a suitable production function is a bottleneck in SFA research.…”
Section: Introductionmentioning
confidence: 99%